Circuit quantum acoustodynamics with surface acoustic waves. Issue 1 (December 2017) - Manenti, Riccardo; Kockum, Anton; Patterson, Andrew; Behrle, Tanja; Rahamim, Joseph; Tancredi, Giovanna; Nori, Franco; Leek, Peter
Abstract The experimental investigation of quantum devices incorporating mechanical resonators has opened up new frontiers in the study of quantum mechanics at a macroscopic level. It has recently been shown that surface acoustic waves (SAWs) can be piezoelectrically coupled to superconducting qubits, and confined in high-quality Fabry–Perot cavities in the quantum regime. Here we present measurements of a device in which a superconducting qubit is coupled to a SAW cavity, realising a surface acoustic version of cavity quantum electrodynamics. We use measurements of the AC Stark shift between the two systems to determine the coupling strength, which is in agreement with a theoretical model. This quantum acoustodynamics architecture may be used to develop new quantum acoustic devices in which quantum information is stored in trapped on-chip acoustic wavepackets, and manipulated in ways that are impossible with purely electromagnetic signals, due to the 105 times slower mechanical waves. In this work, Manenti et al. present measurements of a device in which a tuneable transmon qubit is piezoelectrically coupled to a surface acoustic wave cavity, realising circuit quantum acoustodynamic architecture. This may be used to develop new quantum acoustic devices.